PILU MEMBIRU MUSICAL FORM ANALYSIS BY KUNTO AJI - Bazir, Rizkyatul; Hidayat, Robby; Pristiati, Tutut (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2022)
Musical form is the composition of music in a composition of motifs, themes, and phrases. Musical forms according to the number of sentences is divided into three types, namely one-part musical form, two-part musical form, and three-part musical form. This study aims to describe the musical form of the song